2000
DOI: 10.1148/radiology.217.2.r00nv14456
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Performance in Chest Radiography

Abstract: By using a receiver operating characteristic approach and a standardized set of chest radiographs, observer accuracy and variability are easily quantified. This approach provides a basis for comparing the diagnostic performance of physicians. When value is measured as a diminution in uncertainty, board-certified radiologists contribute substantial value to the diagnostic imaging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 16 publications
3
43
0
3
Order By: Relevance
“…The results of this study (similar to previous studies that investigated variability in the interpretation of chest radiographs and mammograms (23,24)) could have important implications for the clinical interpretation of CT scans in the context of lung nodule detection in which a single reader is responsible for what is clearly a difficult detection task. The question must be raised as to assisting the single reader with a second (or multiple) human reader, or assisting the single reader through the computer-aided diagnosis paradigm.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study (similar to previous studies that investigated variability in the interpretation of chest radiographs and mammograms (23,24)) could have important implications for the clinical interpretation of CT scans in the context of lung nodule detection in which a single reader is responsible for what is clearly a difficult detection task. The question must be raised as to assisting the single reader with a second (or multiple) human reader, or assisting the single reader through the computer-aided diagnosis paradigm.…”
Section: Discussionsupporting
confidence: 83%
“…At the threshold of uncertainty, radiologists can err on the side of making false-positive or false-negative decisions depending on their concern for the consequences of their decisions. 17 Which quality assessment approaches are used depends for the most part on the particular aspects of care being examined. Evaluation programs may be person centered or system centered, and their scope can be department wide, institution wide, or system wide.…”
Section: Assessment Of Accuracymentioning
confidence: 99%
“…The error rates of non-radiology physicians are -not surprisingly -substantially higher than those of radiologists [5,6]. Potchen and colleagues [5] showed that when three groups of physicians (radiologists, radiology residents and non-radiology physicians) were asked to diagnose a standardized set of 60 chest X-rays, the certified radiologists outperformed the radiology residents and the residents performed better than the non-radiologists physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Potchen and colleagues [5] showed that when three groups of physicians (radiologists, radiology residents and non-radiology physicians) were asked to diagnose a standardized set of 60 chest X-rays, the certified radiologists outperformed the radiology residents and the residents performed better than the non-radiologists physicians. Eng et al [6] found similar results when comparing emergency medicine physicians and emergency medicine residents to radiologists and radiology residents.…”
Section: Introductionmentioning
confidence: 99%